Identifying Differential Gene Expression in Wing Polymorphism of Adult Males of the Largest Water Strider: De novo Transcriptome Assembly for Gigantometra gigas (Hemiptera: Gerridae). Issue 6 (10th December 2018) - Sun, Xiao-ya; Wang, Yan-hui; Dong, Zhuo-er; Wu, Hao-yang; Chen, Ping-ping; Xie, Qiang
Abstract: Wing polymorphism is common in a wide variety of insect species. However, few studies have reported on adaptations in the wing polymorphism of insects at molecular level, in particular for males. Thus, the adaptive mechanisms need to be explored. The remarkable variability in wing morphs of insects is well represented in the water striders (Hemiptera: Gerridae). Within this family, Gigantometra gigas (China, 1925), the largest water strider known worldwide, displays macropterous and apterous males. In the present study, we used de novo transcriptome assembly to obtain gene expression information and compared body and leg-component lengths of adult males in different wing morphs. The analyses in both gene expression and phenotype levels were used for exploring the adaptive mechanism in wing polymorphism of G. gigas . After checking, a series of highly expressed structural genes were found in macropterous morphs, which were related to the maintenance of flight muscles and the enhancement of flight capacity, whereas in the apterous morphs, the imaginal morphogenesis protein-Late 2 (Imp-L2 ), which might inhibit wing development and increase the body size of insects, was still highly expressed in the adult stage. Moreover, body and leg-component lengths were significantly larger in apterous than in macropterous morphs. The larger size of the apterous morphs and the differences in highly expressed genes between the two wing morphs consistently demonstrate the adaptive significance of wing polymorphism in G. gigas . These results shed light on the future loss-of-function research of wing polymorphism in G. gigas .